Determinants of Corporate Philanthropy: A Case of Karachi Stock Exchange - Uzma Bashir (International Econometric Review (IER), 2017)
Corporate Philanthropy (CP) has become increasingly important as a means of filling gaps in the provision of social services using Public-Private partnerships. Very little research exists on determinants and motives of CP in Pakistan. This paper utilizes data from the 2001-2011 Annual Reports of 234 firms listed on the Karachi Stock Exchange (KSE) to analyze the association of CP with different firm specific factors like firm size, firm visibility, labor intensity, firm's financial position (measured as profitability, leverage, cash and equivalent balance, and dividend payout), and the impact of natural disasters on CP. Because this is the first study on this data set, we have employed exploratory data analysis techniques and carefully consider the impact of outliers and other non-standard features of the data. We have used Panel data analytic techniques as well as the Tobit model to analyze the associations between different firm specific factors and CP. We found that firm size, prior profitability, and natural disaster have significant positive impact on CP. We found no evidence that firms are using philanthropy for image creation. Furthermore, exploratory data analysis shows that there are some clusters of firms, which behave differently. Standard regression analysis techniques cannot deal with such cases that require more sophisticated treatment.
Keywords: D64; L11; Q54; C38; 330; Philanthropy; Firm Size; Natural Disaster; Clusters